2014
DOI: 10.1016/j.freeradbiomed.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

AKT/mTOR and c-Jun N-terminal kinase signaling pathways are required for chrysotile asbestos-induced autophagy

Abstract: Chrysotile asbestos is closely associated with excess mortality from pulmonary diseases such as lung cancer, mesothelioma, and asbestosis. Although multiple mechanisms in which chrysotile asbestos fibers induce pulmonary disease have been identified, the role of autophagy in human lung epithelial cells has not been examined. In the present study, we evaluated whether chrysotile asbestos induces autophagy in A549 human lung epithelial cells, and then analyzed the possible underlying molecular mechanism. Chrysot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
(80 reference statements)
2
22
0
Order By: Relevance
“…A previous study by our group revealed that p53 mediated PM-induced alveolar epithelial cell mitochondria-regulated apoptosis (13). It was also confirmed that the Akt/mTOR and c-Jun N-terminal kinase (JNK) signaling pathways were involved in chrysotile asbestos-induced autophagy in human lung epithelial cells (A549) (14). In the present study, the effect of PM 2.5 on the induction of autophagy in vitro and the potential underlying mechanisms were evaluated.…”
Section: Introductionsupporting
confidence: 64%
“…A previous study by our group revealed that p53 mediated PM-induced alveolar epithelial cell mitochondria-regulated apoptosis (13). It was also confirmed that the Akt/mTOR and c-Jun N-terminal kinase (JNK) signaling pathways were involved in chrysotile asbestos-induced autophagy in human lung epithelial cells (A549) (14). In the present study, the effect of PM 2.5 on the induction of autophagy in vitro and the potential underlying mechanisms were evaluated.…”
Section: Introductionsupporting
confidence: 64%
“…Many reported studies support the conclusion that MAPK8/9 plays an essential role in the promotion of autophagy [523]. In contrast, our analysis does not indicate a major role for MAPK8/9 in starvation-induced autophagy.…”
Section: Discussionsupporting
confidence: 64%
“…This mechanism of MAPK8 signaling is mediated by BCL2 (B cell leukemia/lymphoma 2) phosphorylation (on Thr69, Ser70, and Ser87) that disrupts the interaction of BCL2 with BECN1 (beclin 1, autophagy related) and initiates BECN1-dependent autophagy [5]. Subsequent studies have provided strong support for this role of MAPK8 in autophagy [619], although contributing roles for MAPK9 [2023] and alternative potential functions of MAPK8 related to autophagy have also been reported [2429]. …”
Section: Introductionmentioning
confidence: 99%
“…We speculate that NF-κB p65 regulated the expression of the autophagyassociated protein LC3B and controlled the expression of p53 to control the expression of Bcl-2 family proteins in BMA155Cl-induced HepG-2 cells. Considering the complexity of intracellular signal transduction, other signaling proteins, such as p38 and AKT, may also play important roles in BMA155Cl-induced autophagy and apoptosis in HepG-2 cells [42] . Our results suggest that the BMA-155Cl-induced inhibition of HepG-2 cell growth via autophagy and apoptosis might be a promising anti-tumor candidate.…”
Section: Discussionmentioning
confidence: 99%